Growth and Yield Responses of Various Nutrient Efficient Maize Lines to Application of Low Doses of Biological Fertilizers and Chemical Fertilizers in Different Growing Seasons - Yopie Moelyohadi; A. Haitami; Nariman Hadi (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Through the use of low dosages of chemical fertilizers and effective nutrient-corn genotypes that respond to bio-fertilizer type assignments, this study intends to produce rather steady outcomes over the course of several growing seasons. Field tests for this study have been conducted at the ATP Ministry of Research and Technology in South Sumatra. The experiment was run across two growing seasons: the dry season (May through September 2011) and the rainy season (January–April 2012). The equal split-split plot design is used for the study's two growing seasons. The central conflict concerns the application of chemical fertilizer at the following rates: P1: 50% standard dose of ATP (200 kg urea, 50 kg SP36, and 25 kg KCl ha-1), and P2: 25% standard dose of ATP (100 kg urea, 25 kg SP36, and 12,5 kg KCl ha-1). Treatment of several biological fertilizer subplots: H0: no biological fertilizer (control); H1: mycorrhiza; H2: bacterial phosphate solvent. The treatment of children plot uses a variety of corn strains with effective nutrient selection outcomes, including strains B41 (G1), L164 (G2), S219 (G3), and variations BISI 816, as the genotype comparison (G4). Three times each was used for each combination of treatments. The results of the two investigations indicate that strain B41 can produce adaptive growth based on the growing season, is more resilient to drought stress, and may be able to produce more at lower doses of chemical fertilizer while being comparatively stable. A combination of chemical fertilizer at the 50% standard dose of ATP and mycorrhizal fertilizer, along with strain B41, has the best impact on the growth and yield of maize on marginal dryland. Mycorrhizae fertilizer at various levels of low doses of chemical fertilizer can increase the growth and yield of maize in two different cropping seasons. All of the examined maize lines generally showed the ability of the bacteria connected to mycorrhizal and phosphate solvents to enhance nutrient absorption